Collaborating for community food security: Emerging scholar participation in a community–university partnership. Issue 4 (December 2017) - Nelson, Erin; Dodd, Warren
In recent years, there has been rapid growth in community–university partnerships. As part of this trend, emerging scholars, including graduate students and postdoctoral fellows, have demonstrated significant interest in being part of community-engaged research projects. However, while there is a growing body of literature on the general subject of CU partnerships, the perspective of emerging scholars is not adequately addressed. In this paper, we aim to address that gap by presenting the case of a specific partnership – one that focused on the issue of community food security – and highlighting the role played by emerging scholars. We suggest that some of the challenges and opportunities characteristic of CU work affect emerging scholars, and the partnerships in which they are involved, in unique ways. Because we view emerging scholar participation in engaged research as valuable for both researchers and community partners, we argue in favour of developing institutional spaces that can support their involvement in CU partnerships by providing opportunities to do the work, facilitating skill building and creating communities of practice.